Influence of exit opening location on mixed convection in a channel with volumetric heat sources - Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2010)
Mixed convection heat transfer in a channel with volumetric heat source and different opening ratio at the exit has been analyzed numerically. Steady, laminar, two-dimensional model based on the finite-volume method is used for solving the mass, momentum and energy transfer governing equations. The flow is injected to the duct with a uniform velocity distribution. The problem is studied in three aspect ratios (A = 1, 3 and 5) and three opening cases as single opening near the ceiling, single opening near the bottom and double openings. The study is also tested for different Richardson numbers between 0.01 and 10. Streamlines, isotherms, Nusselt numbers and temperature profiles were obtained for indicated cases. It is found that both the Richardson number and the locations of exit openings have strong effects on flow and temperature distribution in the presence of volumetric heat sources. The highest heat transfer was formed when the outlet port is located onto top of vertical wall. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Internal heat generation; Open cavity; Mixed convection